The stolen sapphire : a Samantha mystery - Buckey, Sarah Masters, 1955- (Middleton, WI : Pleasant, 2006)
Samantha investigates when a valuable jewel is stolen during an ocean liner's transatlantic crossing to Europe.
"American girl."
"American Girl mysteries".
Includes historical information about crossing the Atlantic on ocean liners.
009-up.
Accelerated Reader AR
Keywords: Transatlantic voyages -- Juvenile fiction; Theft -- Juvenile fiction; Transatlantic voyages -- Fiction; Voyages and travels -- Fiction; Stealing -- Fiction; Mystery and detective stories; Historical fiction; Mystery fiction; Historical fiction